PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL, KECERDASAN SPRITUAL, DAN KECERDASAN SOSIAL TERHADAP PEMAHAMAN AKUNTANSI - Herli, Fauzi; Silfi, Alfiati; ', Kamaliah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to know Empirically emotional quotient influence, the intelligence intellectuals, intelligence and spiritual intelligence to understanding accounting. This research data collection for using questionnaires . Questionnaire distributed, at 4 Universities that are in Pekanbaru, Riau University , University of Islam, Universitas Islam Negeri Riau Suska Riau, and University of Yellow Lancang, with the number of respondents each of them as much as 50 respondents every University. Based on the result to disseminate kuesionir collected sebanyak 132 questionnaires that can be processed. Data analysis done by using computer programs that help SPSS (Statistical Package For Social Science) Versi. 0.17 . A tool for analysis that used in this research multiple regression analysis is a double.Results of the study showed that the emotional quotient, the intelligence intellectuals, the intelligence and spiritual intelligence social influence on the understanding accounting. With the significant emotional quotient 0,000, intellectual 0,000, intelligence spiritual 0,029 and 0,000 social intelligence. The alpha of 0.05 . The R Square of 0.97 which means 97% independent software vendors variables affect the interplay between, while the rest of 3.0 percent is influenced by other factors outside this discussion such as teenage learning, attending seminars, training and also activities outside class, etc.Keywords : Emotional Quotient. Intellectual, the intelligence Spiritual, intelligence , understanding Accounting.